The tension between international regulation and the autonomy of the EU legal order : The compliance of the EU regarding the access to justice rules of the Aarhus Convention - Simonen, Emmi (My University, 2019)
The question of who is entitled to challenge decisions in the field of environmental law is increasingly relevant. As the Compliance Committee of the Aarhus Convention claimed the EU being in non-compliance with its obligations of providing the members of public a legal right to review acts relating to the environmental matters, it engaged into the continuous debate on the EU locus standi rules and the notion of the complete system of judicial protection. The goal of this master’s thesis is two-folded: first, it examines whether the EU is in non-compliance with its international obligations under Arts 9(3) and 9(4) of the Aarhus Convention, namely the access to justice. This question is linked to the status of the international agreements in the EU legal order and private applicants’ possibilities to challenge EU measures both directly at the EU level and indirectly via national courts. Second, different initiatives for the way forward are being analyzed. The primary approach of the thesis is legal positivism, anchored to the school of critical legal studies. The approach of postnational constitutionalism is also being incorporated. The EU is in non-compliance with its obligations regarding the access to justice rules of the Aarhus Convention. The indirect route to the Court of Justice of the European Union cannot compensate for the failure of not providing the members of the public access to justice in environmental matters directly. The best way forward is to amend the internal review mechanism under the Aarhus Regulation. The EU is encouraged to carefully examine the consequences when acceding into various international agreements.

Kysymys oikeuden saatavuudesta ympäristöoikeuden saralla on relevantimpi kuin koskaan. Århusin sopimuksen vaatimusten noudattamista käsittelevä komitea linjasi, että EU ei noudata velvollisuuksiaan antaa yleisöön kuuluville henkilöille oikeus turvautua hallinnollisiin ja tuomioistuinmenettelyihin sellaisten ympäristöön liittyvien toimien osalta, jotka saattavat olla ristiriidassa EU-lainsäädännön kanssa. Samalla komitea osallistui pitkään jatkuneeseen keskusteluun kanneoikeudesta sekä täysin kattavan oikeussuojakeinojen että -menettelyiden järjestelmästä EU:ssa. Tämän pro gradu- tutkielman päämäärä on kaksiosainen: työssä tutkitaan, noudattaako EU Århusin sopimuksen 9(3) ja 9(4) artikloissa säädettyjä muutoksenhaku- ja vireillepano-oikeuteen liittyviä velvoitteitaan. Ensimmäinen tutkimuskysymys on yhteydessä kansainvälisoikeudellisten sopimusten soveltamiseen EU:n oikeusjärjestelmässä sekä luonnollisten henkilöiden että oikeushenkilöiden mahdollisuuksiin nostaa kanne EU:n säädöksiä vastaan joko suoraan EU-tasolla tai epäsuorasti kansallisessa tuomioistuimessa. Tutkielman toisessa osassa esitetään mahdollisia jatkotoimenpiteitä EU:lle. Työn metodi on pääosin oikeuspositivistinen, mutta se sisältää myös oikeuden kriittisen tarkastelun piirteitä. Näkökulma on myös osin konstitutionalistinen. EU ei noudata kansainvälisoikeudellisia velvoitteitaan Århusin sopimuksen muutoksenhaku-ja vireillepano-oikeuden osalta. Epäsuora reitti EUT:een ei korvaa yleisöön kuuluvien henkilöiden suppeaa mahdollisuutta nostaa kanne ympäristöoikeudellisissa asioissa suoraan EU:n tasolla. Århusin asetuksen muuttamista suositellaan ensisijaisena vaihtoehtona. Jatkossa EU:n kannattaa tarkasti arvioida kansainvälisten sopimusten vaikutukset sen autonomiseen oikeusjärjestelmään.
Keywords: EU law, international law, procedural law, environmental protection, access to justice